2011
DOI: 10.1136/bcr.07.2010.3156
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent granulomatous mastitis mimicking inflammatory breast cancer

Abstract: Granulomatous mastitis (GM) is an uncommon benign breast lesion. Diagnosis is a matter of exclusion from other inflammatory, infectious and granulomatous aetiologies. Here, we presented an atypical GM case, which had clinical and radiologic features overlapping with inflammatory breast cancer (IBC). The disease had multiple recurrences. The patient is a 40-year-old Caucasian woman with a sudden onset of left breast swelling accompanied by diffuse skin redness, especially of the subareolar region and malodorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 26 publications
(39 reference statements)
0
35
0
Order By: Relevance
“…Many previous studies have shown that recurrences after surgical excision are frequent, even after bilateral mastectomy. [8][9][10][11]14,17,18,[21][22][23][24] Additionally, breast cancer has never been reported as a co-existent finding in patients with granulomatous mastitis.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Many previous studies have shown that recurrences after surgical excision are frequent, even after bilateral mastectomy. [8][9][10][11]14,17,18,[21][22][23][24] Additionally, breast cancer has never been reported as a co-existent finding in patients with granulomatous mastitis.…”
Section: Resultsmentioning
confidence: 91%
“…8,9,[10][11][12][13] Recurrence or residual disease, however, may still occur after mastectomy. 10,11,14 Currently, surgical management has become less prominent in its management and non-surgical M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 recommendations have become more common including medications (i.e., steroids, methotrexate, azathioprine, tuberculosis medications) or close observation. 8,9,15,16 One study found that patients underwent spontaneous resolution in 14.5 months.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics, steroids, and surgery are the options from the least to the most aggressive [13]. Antibiotics are widely used but the most effective noninvasive treatments are corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The disease, was first described by Kessler and Wollock in 1972 (5). Although it is a benign condition, it is important from different points of view: 1-it poses a diagnostic and treatment dilemma (2, 3), also, it clinically and mammographically mimics breast cancer, especially inflammatory type (4).…”
Section: Introductionmentioning
confidence: 99%